Demographic Factors as Disparities in Sabah Values of Patriotism - Mohd Rahimi, Ramli; Mazli, Mamat; Asilatul Hanaa, Abdullah; Faezah, Kassim; Muhammad Shamshinor, Abdul Azzis; Fatimi, Hanafi (UTHM, 2023)
The main challenges of nation -building is to manage and organize the social differences of society, is by sharing the same values ​​of patriotism. The value of patriotism that can be shared without differentiating between ethnic and religious identities will make it easier to cultivate and maintain harmonious relations in a society that is complex. Therefore, the purpose of this paper is to examine the practice of the Kadazan-Dusun, Bajau and Murut communities on the value of patriotism as their identity as Malaysian citizens. The values ​​of patriotism in this study are based on six values, namely loyalty, sacrifice, pride, sense of belonging, discipline, striving and productivity. The domain of practicing the value of patriotism is based on five frequency scales. The finding scores of this section are divided into three levels, namely high, moderate and low. The study involves 500 respondents consisting of Kadazan-Dusun, Bajau and Murut ethnic groups. This study is based on a quantitative research approach and uses the Probability Proportional to Size (PPS) sampling method. Study data were obtained through survey method with the distribution of questionnaires to respondents from selected districts in Sabah. The findings of this study were analyzed descriptively and inferentially. The results of the study found that the respondents' practice of patriotism values ​​is high and there is a significant difference between ethnic and religious factors on the practice of patriotism values. It can be concluded that the society in Sabah is a patriotic society, but ethnic and religious factors also determine the differences in patriotic practices between the Kadazan-Dusun, Bajau and Murut ethnic groups.